Comparison of luminescence detectors of Al2O3:C, CaF2:Mn, LiF:Mg, Cu, P and quartz with respect to retrospective dose reconstructions using bricks. (December 2021) - Ekendahl, Daniela; Kurková, Dana; Judas, Libor; Čemusová, Zina; Reimitz, Dan; Kubínová, Marie; Kapuciánová, Michaela; Hupka, Ivan
Abstract: In the aftermath of an orphan radiation source find, a complex retrospective dose reconstruction can be required to estimate doses of persons who were staying in the vicinity. In retrospective dose reconstructions based on luminescence measurements of quartz extracted from bricks, high sensitivity thermoluminescence detectors (TLD) can be used as an ancillary tool for dose distribution measurements or natural radiation background measurement. We investigated the potential and limits of Al2 O3 :C, CaF2 :Mn and LiF:Mg, Cu, P detectors for such applications. We measured depth-dose profiles in bricks using quartz and the TLDs. We factored in important dosimetry characteristics such as dose response, energy response and detection threshold. The work included Monte Carlo simulations. Depth-dose profiles and radiation spectra inside of the bricks were calculated for purposes of comparison and interpretation. The measurements and calculations were performed for two different photon spectra with mean energies of 662 and 118 keV. As regards comparison of the measured and Monte Carlo calculated depth-dose profiles, the best agreement was found for LiF:Mg, Cu, P. Quartz, Al2 O3 :C and CaF2 :Mn tend to overestimate dose for lower photon energies and greater depths in bricks. The overestimation was the most marked for CaF2 :Mn. For measurements related to quartz, especially for natural radiation background dose measurement, the most suitable TLDs are Al2 O3 :C and LiF:Mg, Cu, P. CaF2 :Mn is the least useful material. Highlights: Quartz and luminescence detectors were compared under defined conditions for purposes of retrospective dosimetry.. Depth-dose profiles in bricks measured using the detectors and calculated are in a good agreement for 137 Cs exposure. Quartz, Al2 O3 :C and CaF2 :Mn tend to overestimate dose for lower photon energies at greater depths in bricks (>4 cm). Photon spectrum and its possible modifications with depth in bricks should be taken into account when selecting suitable detectors. Al2 O3 :C and LiF:Mg, Cu, P are suitable ancillary detectors for some dose measurements related to quartz.